Sagot :
Answer:
Step-by-step explanation:
x - 3 = -1 x - 3 = 1
x = 2 x = 4
SOLUTION:
[tex] \tt |x - 3| = 1[/tex]
[tex] \sf solve \: the \: absolute \: value \\ \tt |x - 3| = 1 \\ \sf we \: know \: either \\ \tt x - 3 = 1 \: \sf or \: \tt x - 3 = - 1 \\ \\ \tt x - 3 = 1 \: \sf (possibility1) \\ \tt x - 3 + 3 = 1 + 3 \:\sf (add \: 3 \: both \: sides) \\ \tt x = 4 \\ \\ \tt x - 3 = - 1 \sf (possibility2) \\ \tt x - 3 + 3 = - 1 + 3 \: \sf (add \: 3 \: both \: sides) \\ \tt x = 2 \\ \\ \sf \large answer \\ \tt x = 4 \:and\:x = 2[/tex]
#CarryonLearning